2021
DOI: 10.1038/s41398-020-01128-2
|View full text |Cite
|
Sign up to set email alerts
|

Gray and white matter morphology in substance use disorders: a neuroimaging systematic review and meta-analysis

Abstract: Substance use disorders (SUDs) are characterized by a compulsion to seek and consume one or more substances of abuse, with a perceived loss of control and a negative emotional state. Prolonged substance use seems to be associated with morphological changes of multiple neural circuits, in particular the frontal–striatal and limbic pathways. Such neuroadaptations are evident across several substance disorders, but may vary depending on the type of substance, consumption severity and/or other unknown factors. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(58 citation statements)
references
References 78 publications
3
52
3
Order By: Relevance
“…This important work showed small to moderate effect sizes ( g = 0.304, SD = 0.134) but did not test for convergence of imaging results in order to draw conclusions about the location of altered WM in AUD. A recent large-scale meta-analysis focused on gray and white matter morphology across all substance use disorders and indicates general and substance-specific structural brain changes in patients compared with healthy controls [ 26 ]. Sub-analysis regarding AUD in specific revealed convergent WM alterations in regions of the corticospinal tract and anterior thalamic radiation.…”
Section: Introductionmentioning
confidence: 99%
“…This important work showed small to moderate effect sizes ( g = 0.304, SD = 0.134) but did not test for convergence of imaging results in order to draw conclusions about the location of altered WM in AUD. A recent large-scale meta-analysis focused on gray and white matter morphology across all substance use disorders and indicates general and substance-specific structural brain changes in patients compared with healthy controls [ 26 ]. Sub-analysis regarding AUD in specific revealed convergent WM alterations in regions of the corticospinal tract and anterior thalamic radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Other adult sMRI studies have shown no neuroanatomical differences between CU adults and age-matched controls ( 11 , 22 ). Notably absent from this literature are GMV studies in adults that show increased cortical thickness or GMV in relation to cannabis use ( 21 ), although one or two studies have reported increased volumes in non-cortical regions including the striatum ( 23 ) and cerebellum ( 15 ). In contrast, based upon systematic examination of the adolescent sMRI literature [see ( 24 ) for review], more variability in morphologic findings is seen, and the opposite pattern of cannabis-related GMV abnormalities is observed, with a number of studies showing larger GMV volumes in CU compared to typically-developing (TD) youth ( 12 , 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies report mixed findings and that the direction of the association between substance use and structural MRI measures depends on the specific substance and the region of interest. 45,46…”
Section: Discussionmentioning
confidence: 99%